Supporting the learning experience of health‐related profession students during clinical placements with technology: A systematic review. Issue 2 (16th August 2022) - Jones, Andrea; Wilson, Iseult; McClean, Stephen; Kerr, Danny; Breen, Cathal
Abstract: High quality clinical education is a fundamental component of undergraduate health‐related professions programmes. Technological interventions offer potential to support and enhance student learning experiences during clinical placements, i.e. away from the university setting. This review aims to systematically explore, evaluate and summarise the range of technological strategies within the literature regarding support of the student learning experience during clinical placements. A systematic review was conducted using defined search terms, educational and medical subject headings (MeSH). Relevant databases were searched alongside hand searching of citations and grey literature. Experimental studies with technological strategies designed to support student learning during clinical placements were included. A modified version of Kirkpatrick's levels (Barr et al., Effective interprofessional education: Assumption, argument and evidence . Blackwell, 2005) was used to evaluate strategies. Twenty‐one papers met inclusion criteria. Heterogeneity existed in terms of strategies and their usage e.g. whether synchronous or asynchronous; targeting individual students or groups A wide range of technological strategies may be employed to support the student learning experience during placements. However, none were identified as being of high quality therefore further research is required to provide stronger evidence to support their use. Consideration should be given to the underlying purpose of the strategy as well as the potential barriers for implementation e.g. acceptability and connectivity. Students should be clearly informed of strategy purpose and requirements, with opportunities to practice prior to placements. Review findings may provide insight to assist educators to develop future support strategies for students on clinical placements during challenging circumstances such as the COVID‐19 pandemic. Context and implications Rationale for this study This systematic review aimed to establish and describe technological methods that are currently being used during clinical placements to support the learning experience of undergraduate students of health‐related professions. Why the new findings matter The findings indicate that a broad range of technological strategies may be utilised to support the student learning experience during placements, with numerous learner benefits including improved clinical knowledge, increased reflection upon practice, increased peer and staff support, and reduced sense of isolation during placements. Implications for educators Educators should clearly explain the strategy purpose and requirements of the student should be clearly explained, with opportunities provided for students prior to placements to practice its use. Balance is required in terms of (a) encouraging student engagement without over burdening the student and (b) moderator involvement to facilitate student engagement without stifling contributions. When selecting a technological support strategy, consideration should be given to (a) potential technological difficulties, such as accessing platforms and (b) acceptability of the strategy for use within a clinical context.